Analyses of the Factor Structure and Item Measurement Bias of a School Climate Scale in Chilean Students - Calderón, Francisca; González, Jorge (Frontiers in Education, 2021)
School Climate is an essential aspect in every school community. It relates to perceptions of the school environment experienced by various members of the educational system. Research has shown that an appropriate school climate impacts not only on the quality of life of all members in the educational system, but also on learning outcomes and education improvements. This study aims to explore a measure of School Climate which is included in a questionnaire applied to Chilean students, parents and teachers, that provides information related to the personal and social development of the students at Chilean educational institutions. We investigate the factor structure of the items composing the School Climate construct, and evaluate the potential presence of Differential Item Functioning (DIF) between male and female groups. Using a questionnaire applied to a sample of students attending 10th grade, the results indicated a multidimensional structure of the School Climate construct and that measurement bias for male and female groups exist in some of the items measuring the construct.